The motives of learning activity and intellect of students - Dževečka, A. (Psichologija, 1984)
The progress in studies is conditioned by the level of functional and motivational components and their correlation. Peculiarities of visual memory, space imagination and thinking of students of physics and technical specialities are analysed in this work. One of the most important motives for studying physics and technics is interest in the subjects. The author considers that the peculiarities of space imagination and thinking are constituent parts of the intellectual basis for the students’ interest in physics and technical subjects.
Keywords: visual memory; space imagination; spatial imagination; thinking; motives of learning activity; intellect; intelligence